A PROSPECTIVE OBSERVATIONAL COMPARATIVE STUDY OF BACLOFEN AND LIBRIUM IN ALCOHOL WITHDRAWAL SYNDROME - SUJANA DEVIREDDY; SUNDARAMOORTHI REVATHI; KUMAR B (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: The objective of the study was to evaluate the safety, effectiveness, and anti-craving properties of baclofen and Librium (chlordiazepoxide) in patients with alcohol withdrawal syndrome (AWS). Methods: This was a prospective observational study including patients with a history of alcohol consumption and diagnosed with AWS. Participants were treated with baclofen and Librium. The Clinical Institute Withdrawal Assessment (CIWA) scale was used to assess the severity of withdrawal symptoms. The effectiveness of baclofen and Librium was evaluated based on symptomatic relief. Results: Out of 492 patients screened, 367 subjects were attended 3 follow-ups and provided information regarding effectiveness of baclofen, Librium, and improvement of their quality of life. Both baclofen and Librium produced a significant reduction in CIWA-Ar scores. Analysis of individual CIWA-Ar subscales showed that both drugs significantly reduced sweating, tremors, and anxiety. Although Librium showed a faster onset of effect than baclofen, baclofen has greater anti-craving properties for alcohol. Conclusion: Librium and baclofen both consistently reduced the overall CIWA-Ar scores. Compared to Baclofen, chlordiazepoxide offered faster and more efficient alleviation from the symptoms of alcohol withdrawal. AWS was another condition for which Baclofen demonstrated encouraging results. Baclofen shows comparable efficacy to Librium in the treatment of AWS, suggesting its potential role as an alternative therapy.